"PREVENTING REDUNDANCY AND ENSURING MEANING RETENTION IN TRANSLATION" THE PROCESS OF TRANSLATION OF LORD JIM BY JOSEPH CONRAD. - Jumayeva Mavluda Anvar qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: The topic "Preventing Redundancy and Ensuring Meaning Retention in Translation" is crucial for translators as it helps in ensuring that the text is expressed clearly and concisely. One of the translator’s main tasks is to eliminate unnecessary repetition and choose words that convey the intended message accurately, preserving both the clarity and the essence of the original text. This involves using synonyms and collocations appropriately, understanding cultural nuances, and ensuring that the grammar and style remain aligned with the target language while maintaining the integrity of the original content.